Ajuga reptans: Common Bugle, Bugleweed, Carpet Bugleweed - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document provides an overview of Ajuga reptans, commonly known as bugleweed. It describes the plant’s characteristics, including its dark green to purple leaves, small blue flowers, and its growth habit as a ground cover. The document also details its planting requirements, such as preferred light conditions, soil tolerances, and USDA hardiness zones. Additionally, it highlights the plant’s uses in landscaping, potential invasive nature, and available cultivars. The document concludes with information on propagation, pest resistance, and aesthetic considerations for garden design. Original publication date October 1999.